Brave old world: Accounting for 'high-tech' knowledge in 'low-tech' industries - Mendonça, S. (Research Policy, 2009)
‘Lower-tech’ sectors are still commonly regarded as unusual suspects in the modern process of innovation and economic change. In this paper we try to understand better how organisations specialising in traditional businesses have been transformed by a period of paradigm-shift such as the one that characterised the final decades of the twentieth century. We focus on a population of nearly 500 of the world's largest innovative companies to assess the extent to which companies belonging to ‘old-economy’ sectors have been developing cutting-edge knowledge about clusters of new technologies such as ICT, new materials and biotechnology. We find that ‘non-high-tech’ corporations transformed their patent portfolios in a non-trivial way. Companies in mature trades contributed significantly to the development of technologies that are at the core of the so-called Third Industrial Revolution.